The Role of Spastin in Axon Biology - Costa, Ana Catarina; Sousa, Monica Mendes (Frontiers in Cell and Developmental Biology, 2022)
Neurons are highly polarized cells with elaborate shapes that allow them to perform their function. In neurons, microtubule organization – length, density, and dynamics – are essential for the establishment of polarity, growth, and transport. A mounting body of evidence shows that modulation of the microtubule cytoskeleton by microtubule-associated proteins fine tunes key aspects of neuronal cell biology. In this respect, microtubule severing enzymes – spastin, katanin and fidgetin – a group of microtubule-associated proteins that bind to and generate internal breaks in the microtubule lattice, are emerging as key modulators of the microtubule cytoskeleton in different model systems. In this review, we provide an integrative view on the latest research demonstrating the key role of spastin in neurons, specifically in the context of axonal cell biology. We focus on the function of spastin in the regulation of microtubule organization, and axonal transport, that underlie its importance in the intricate control of axon growth, branching and regeneration.